KKM TEMATIK KELOMPOK 53 SEBAGAI BENTUK PENGABDIAN KEPADA MASYARAKAT DI DESA PAMANUK KECAMATAN CARENANG KABUPATEN SERANG - Fatari Fatari; Moh. Darip; Gatot Hartoko; Romani Romani; Anggun Fitriani; Listantiana Listantiana; Dimas Hardiansyah (Jurnal Abdimas Bina Bangsa, 2021)
Community service activities through Student Work Lectures (KKM) aim to assist local government activities in carrying out development in villages/kelurahan; Growing public awareness to improve the quality of life of the nation and state; Fostering community motivation towards activities in the village development process; Help socialize the prevention of Covid-19 transmission and socialize the importance of Vaccination; Provide information and imaging of the existence of Bina Bangsa University College. The targets are expected to be achieved, namely: Able to run eight work programs that have been set, provide skills and take an active role in village development. Students who have a high sense of sensitivity to the problems and difficulties faced by the community in community empowerment. Produce students as motivator, problem solving and mentoring figures. The method of implementing this activity is socialization and training by directly involving the Pamanuk village community and high school students in the village. Some of the results achieved in this activity are from the achievements of eight work programs, including; provide understanding to the public about health through outreach and counseling activities, computer training activities for high school students, mentoring activities in the MSME sector and the field of Appropriate Technology that can be utilized by the community, especially in Pamanuk village, Carenang district, Serang district